Implementasi Sistem Informasi Akuntansi pada Usaha Dagang dengan Metode Pengembangan Perangkat Lunak Waterfall - Ismarmiaty, Ismarmiaty; Irfan, Pahrul; Al Faras, Daffa ilyas (Universitas Bumigora, 2024)
Dafifa is engaged in the savings and loan trading business which was founded in 2008 until now. The problem faced is that the preparation of daily financial reports is still done manually with a ledger. The proposed solution is to implement a website-based accounting information system, which is required by trading businesses to process customer data, process loan transactions and financial reporting. The method used in this study is the waterfall software development method, namely the stages of analysis, design, coding and testing. The conclusion from the study is that the website-based accounting information system at UD. Dafifa has been successfully implemented in accordance with the analysis and design. In addition, the results of testing on users show that this application is considered to be in accordance with user needs to be able to process transaction data to financial reporting more effectively and efficiently.